Open Design in Practice : Designers in Residence Kortrijk 2014. - Bouchez, Hilde; Van Durme, Jessy (Kortrijk : Designregio Kortrijk, 2015)
Carratù, Antonio ; Barouillet, Lucie ; Andersson, Robin
boek
Keywords: Carratù, Antonio; Barouillet, Lucie; Andersson, Robin